A internacionalização do setor vitivinícola no Rio Grande do Sul: uma análise sob a lente teórica da visão baseada em recursos - Piveta, Maíra Nunes (2018)
In recent years the attention of several economic sectors in Brazil has strengthened towards the foreign market. Internationalization has received notoriety as an important strategic challenge faced by companies in facing the fierce competition in the domestic market. Therefore, the internationalization process requires companies to have several factors that will enable them to perform their activities in a satisfactory manner in international markets. Resources are one of these factors. Hence winemaking is one of the sectors most severely affected. The Brazilian wine sector, which concentrates most of its production in the state of Rio Grande do Sul, has been highlighted by its growth in the wine and derivatives world market share. In addition, a trend in betting on the formation of the integrated sector projects (PSI) has been observed, which seeks to train, guide and promote the wine companies and the foreign market, an example of this is the Wines of Brazil project. Under this perspective, emerges the overall objective of this research: describe and analyze how resources from the wine industry and the PSI Wines of Brazil are linked to the internationalization of this sector in Rio Grande do Sul, under the perspective of the 3 actors involved in the process. To meet the objective defined in this research, the present study was carried out through a descriptive research with a qualitative approach and was operationalized through the collection of primary and secondary data. The primary data were configured in the application of a semi structured interview script with the three representative respondents of the research subjects (Ibravin, Wines of Brazil and winery "Beta"). The secondary data consisted of documents, reports, printed promotional materials and consultations with public and private companies and organizations websites related to the Rio Grande do Sul wine sector. Regarding the results, the main resources of the evidenced sector were the terroir, the geographical indications, the great geographic concentration of several levels courses related to the winemaking and the great number of institutions of research and promotion existing in the state. About Wines of Brazil resources, the ownership of information and the knowledge that the project centralizes was pointed out with emphasis. In addition, market intelligence through the detection and targeting of actions for the target markets and the formation of the Brazilian wine category were also highlighted. The perceived linkages between resources and the process of internationalization are concrete and occur in a variety of ways. The specificities regarding the terroir of the viticultural regions of Rio Grande do Sul which represent unique properties to the products stand out as an important attribute considered in the international market. However, it was found that the Brazilian wine sector still needs to make significant advances in terms of internationalization, given the low number of exporting companies and the lack of concrete legal and fiscal incentives. Finally, it was noticed that the integration of the wine producing in the foreign market is mainly aimed at the visibility and increase of competitiveness given in the domestic market.